Theoretical Perspectives on Learning: Sunrise Program as an Example for Learning English in the Iraqi Kurdistan Region - Sharif Omer, Talib Muhammad; Mahmood Jukil, Ali (International Journal of Psychosocial Rehabilitation, 2019)
Much has been said about learning as a framework for knowing things and increasing knowledge, but little has been found to deal with theoretical perspectives on learning, especially English as second language learning (L2) in the Kurdistan Region of Iraq (KRI). The significance of learning has long been ignored in Kurdish academic contexts due to a lack of knowledge of the English language learning theories. Linguistically, learning a language refers to a focus on syntactic rules and forms of grammar. Learning is a lifelong process. A gap has been noticed between the theory of learning and actual learning outcomes in the school contexts. The issue is that some students studied English for years, but they still lack the means of effective and meaningful communication. This paper seeks the how of English language learning in the Iraqi Kurdistan school context, particularly to know which theory works well when implemented through the Sunrise program. The findings from the literature review revealed that different theories exist, and each theory has different interpretations and procedures for learning, especially L2 learning. Previous studies conducted by postgraduate scholars show that while the “Sunrise Program,” including its supporting materials and activities, has been well-received by administrators and instructors, the learning of English is still in crisis as students continue to fail to demonstrate competency. Results revealed that students are restricted and not engaged in the actual communication. Despite the Sunrise program being based on the communicative approach, constructive learning is hardly implemented, but the theory of behaviorism is dominated in the current situation of learning English through the Sunrise program in the KRI. In this paper, the qualitative method is adopted because it deals with the PhD theses and MA dissertations, literature, and resources that have been done for the research purposes in KRI. Besides the introduction, this study is divided into five further sections. Foremost is literature, which is an overview of the concept of learning and learning theories. The third section addresses second language and linguistic perspectives. Section four is a methodology, while Section five is an overview of learning English through the Sunrise program in the Iraqi Kurdistan region. The last section is the conclusion, which summarizes the main points throughout this study